THE INFLUENCE OF JOB DESIGN ON THE QUALITY OF WORK LIFE AND JOB SATISFACTION OF EMPLOYEE - Novie Prasetyaning Marhaeni; Noviaty Kresna Darmasetiawan (Journal of Management and Business, 2015)
The research conducted at a flour producer attempts to find out the Influence of Job Design on the Quality of Work Life and Job satisfaction. Primary data was taken through questionnaires method of ninety respondents of the company. The sampling technique is Non-Probability Sampling with purposive random sampling method. While the processing of data using Structural Equation Modelling (SEM) with Partial Least Square (PLS) software. The data processing and the analysis reveal that the result of the three hypotheses can be accepted. The design work gives a positive influence on the quality of work life, while the job design also shows a positive influence on the job satisfaction. The quality of working life also performs a positive effect on employee job satisfaction.